If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5f + 4 + f = 52 Reorder the terms: 4 + 5f + f = 52 Combine like terms: 5f + f = 6f 4 + 6f = 52 Solving 4 + 6f = 52 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6f = 52 + -4 Combine like terms: 4 + -4 = 0 0 + 6f = 52 + -4 6f = 52 + -4 Combine like terms: 52 + -4 = 48 6f = 48 Divide each side by '6'. f = 8 Simplifying f = 8
| 7x-8=3x+16 | | 12+q(5-q)-5q=0 | | -.37x+2=0 | | 7x+8=3x-16 | | 3m+4m=21 | | 20x+50=250 | | x+1-5=6 | | 13x+6=6x-1 | | 4x+2=8x-7 | | 4y+11=7y-28 | | q=0.25p^2-14 | | 5d=95 | | -7x+18=1x-36 | | x^2-7*x+12=0 | | 28=7r | | 27+5x=9+3x | | 5x+4=10x-7 | | 4x+25=6x-45 | | 7x+9=9x-3 | | -3x+17=6x-37 | | 12+4-1= | | 3y+5=5y-1 | | -2x+7=5x-21 | | -2x+7=5x-2 | | 9x^2-27x=-20 | | 20+(-3)(-15)(-19)= | | 5+2+x=2x+6 | | 5x+3=7x-5 | | 8x^2=50x-50 | | 10x^2-11x-35=0 | | 4y+9=7y-15 | | -3(-15)+20(-19)= |